Upaya Meningkatkan Keterampilan Sosial Siswa Dengan Menggunakan Model Cooperative Script Kelas III SD Negeri 019 Rokan IV Koto - Safari, Rio (Science and Education Journal (SICEDU), 2024)
This research was motivated by the low social skills of Class III students at SD Negeri 019 Rokan IV Koto. This research aims to improve students' social skills by using a cooperative script model in Class III learning at SD Negeri 019 Rokan IV Koto. Indicators of social skills are: ability to share, ability to help, ability to follow instructions, ability to express opinions, and ability to accept opinions. This type of research is classroom action research. The subjects of this research were 10 class III students at SD Negeri 019 Rokan IV Koto. The cycle stages in research use planning, implementation, observation and reflection steps. Data collection techniques were carried out using observation techniques. Data analysis techniques use quantitative and qualitative. The research results show that the script cooperative learning model can improve students' social skills. This is shown from the results of observations obtained in cycle I from 10 students, it is known that the social skills of students who fall into the complete category reached 4 students (40%). The results from cycle I to cycle II showed an increase in the social skills of students in the complete category to 8 students (80%). Through the implementation of the cooperative script model, it can improve the social skills of class III students at Sd Negeri 019 Rokan IV Koto